Injuries on Seedlings Caused by Potential Weed in Tropical Rain Forest Regeneration Areas - Sumardi Sumardi; S. M. Widyastuti (Universitas Gadjah Mada, 2000)
The experiment aimed to assess the injuries on Shorea seedlings caused by weed in artificial regeneration of tropical rain forest in Jambi. Four planting systems, strip nurse planting (using Acacia mangium, Paraserianthes falcataria and Gmelina arborea), line planting, gap planting and natural regeneration, were used. Seedling injuries were assessed based on part of seedling suppressed. Results indicated that Shorea seedling suffered from varying degrees of injuries, depending on weed species and part of the seedling suppressed. The dominance of weed and damage intensity were determined by the level of canopy opening on the planting systems. Ground cover dominated rapidly in open canopy, causing up to 55.27% injuries on the seedlings in the strips of G. arborea and P. falcataria. Whereas creepers and vines became dominant in moderate canopy opening. The injury of Shorea seedling planted under nurse tree was determined by the species and planting density of nurse tree used. Light canopy nurse tree such as P. falcataria failed to suppress ground weed, but in the contrary, A. mangium with heavy canopy still allowed creepers and vines to grow.